The fencing lunge: analysis of load distribution to the lower limbs and gender-related differences in young fencers in relation to accident prevention - Sannicandro, I.; Piccinno, A.; Cataleta, R.; Maffione, S.; De Pascalis, E. (Medicina dello Sport, 2010)
Aim. The lunge movement in fencing generates a different force to the two lower extremities. Knowledge of this difference holds importance for reducing the risk of injury, especially among young fencers. The aim of this study was to measure the forces generated to the lower limbs and to determine whether they differed by gender.